Latar Belakang Keluarga dan Pembelajaran Kewirausahaan Pengaruhnya Terhadap Kesiapan Berwirausaha Mahasiswa - Andi Kurniawati; Muhammad Rakib; Agus Syam; Marhawati Marhawati; Muhammad Ihsan Said Ahmad (Universitas Negeri Makassar, 2020)
This study aims to determine the effect of family background and entrepreneurial learning on entrepreneurial readiness of Economic Education Students at State University of Makassar. This study is categorized as a quantitative descriptive study with a population of 350 students, with a total sample of 78 students of Economic Education State University of Makassar 2016-2018 generation. The method of data collection is done by observation, documentation and questionnaire. The analysis technique used is multiple linear regression analysis using SPSS Version 22 software. The results showed that family background and entrepreneurial learning simultaneously had a positive and significant effect on entrepreneurial readiness of Economic Education students at Makassar State University. Partially there is a significant influence between family background and Entrepreneurship Learning on entrepreneurial readiness of Economic Education Students at State University of Makassar